How has sustainable development goals declaration influenced health financing reforms for universal health coverage at the country level? A scoping review of literature - Walter Denis Odoch; Flavia Senkubuge; Charles Hongoro (BMC, 2021)
Abstract Background Achieving universal health coverage (UHC) requires health financing reforms (HFR) in many of the countries. HFR are inherently political. The sustainable development goals (SDG) declaration provides a global political commitment context that can influence HFR for UHC at national level. However, how the declaration has influenced HFR discourse at the national level and how ministries of health and other stakeholders are using the declaration to influence reforms towards UHC have not been explored. This review was conducted to provide information and lessons on how SDG declaration can influence health financing reforms for UHC based on countries experiences. Methods We conducted a rapid review of literature and followed the preferred reporting items for systematic review and meta-analysis (PRISMA) guideline. We conducted a comprehensive electronic search on Ovid Medline, PubMed, EBSCO, Scopus, Web of Science. In searching the electronic databases, we combined various conceptual terms for "sustainable development goals" and "health financing" using Boolean operators. In addition, we conducted manual searched using google scholar. Results Twelve articles satisfied our eligibility criteria. The included articles were analyzed thematically, and the results presented narratively. The SDG declaration has provided an enabling environment for putting in place necessary legislations, reforming health financing organization, and revisions of national health polices to align to the country's commitment on UHC. However, there is limited information on the process; how health ministries and other stakeholders have used SDG declaration to advocate, lobby, and engage various constituencies to support HFR for UHC. Conclusion The SDG declaration can be a catalyst for health financing reform, providing reference for necessary legislations and policies for financing UHC. However, to facilitate better cross-country learning on how SDG declaration catalyzes HFR for UHC there, is need to examine the processes of how stakeholders have used the declaration as window of opportunity to accelerate reforms.